Copper-Catalyzed Oxytrifluoromethylation of Unactivated Alkenes - Zhu, Rong (2012)
A mild, versatile and convenient method for the efficient oxytrifluoromethylation of unactivated alkenes has been developed based on a copper-catalyzed oxidative difunctionalization strategy. This methodology provides access to a variety of classes of synthetically useful CF(3)-containing building blocks from simple starting materials.